Tech reluctance: Fostering empathy for Canadians facing challenges with digital systems - Sebastian Hernandez; Helena Wang; Badr Omrane; Vera Roberts; David Pereyra (Bank of Canada, 2025)
Designing inclusive and user-friendly digital payment systems is crucial to eliminate barriers faced by users. This research focuses on fostering empathy for and identifying the needs of users who exhibit behaviours that indicate they encounter accessibility or usability barriers in digital systems. Specifically, we examine two types of users based on two common behaviours: users who rely on others to perform tasks and those who avoid interacting with technology. The Bank of Canada partnered with the Inclusive Design Research Centre at OCAD University to gain a deeper understanding of these groups. Co-design sessions with end users were used to identify scenarios when cooperative efforts are needed, system features that facilitate supported banking and pain points customers and their support people encounter. The findings show that individuals in the two groups avoid systems they expect lack usability. Addressing these issues through standard accessibility practices, live assistance and thoughtful interface design can enhance user interaction and trust. For accessibility issues that cannot realistically be eliminated, technology that enhances cooperative relationships and allows account owners to control information sharing is key.
Keywords: A14; C90; D83; O33; Y80; 330; Accessibility; Bank notes; Central bank research; Digital currencies and fintech; Digitalization; Financial services